Perceptions of resident physicians on the development of the cardiology resident program during the COVID-19 pandemic in Lima, Peru - Olortegui Yzu, Adriel (2022)
Objective. To describe the perceptions of resident doctors about the development of their training program during the pandemic in the city of Lima - Peru. Materials and methods. Through a cross- sectional study, a questionnaire was applied to seventy-eight cardiology residents in the last two years of training in the specialty. The perceptions about the accompaniment and support of the universities in the educational venues, for the development of the training program in cardiology during the pandemic, were evaluated. Results. Regarding the support provided for their training, the items evaluated showed shortcomings above 60%, where permanent supervision was lacking in 90.0% of the residents. Regarding compliance with the rotations, the residents only received supervision in 24.4%, observing that they did not manage to carry out adequate rotations in 80.8% of the cases. The courses of the curricular plan were adequately developed in 92.5% of the cases, and the actions for the health of the resident were very low, highlighting that only in 9.0% of the cases did the university inquire about the state of health of the resident. Conclusions. The development of the cardiology residency training program during the pandemic presented important shortcomings, showing that the deficiencies were accentuated compared to previous studies.